The Critical Tradition and the Forming of Desacralising Legal Theory - Ivanov, Victor (Research Papers, 2019)
The critical tradition ascending from antiquity through Kant to the present day is in the basic of modern scientific thinking. In the sphere of the legal science, it is threatened by apologetic theories and uncritical positivism. Although the capitalism is rationalistic in its own spirit, there is a danger of its modern hypostases to transform into its irrational dehumanized version, which abandons the most significant achievements of scientific thinking, replacing them with craft pragmatism and professional conformism. In the article is defended the understanding that only the deliberate and purposeful follow-up of the critical tradition and its updating in the conditions of globalizing and digitizing capitalism can give us the foundations of a complete desacralising theory of the state and law.
Keywords: Critical tradition; Critical theory; Crisis of the legal awareness; Desacralising theory of the legal theory; Rationalism